Synthesis and Spectroscopic Characterization of DTPA-Bis Anhydride-Tyramine Derived Metal Complexes: UV-Visible, Photoluminescence Studies and Cytotoxic Evaluations - Nandini, B.; Selvi, M. Amutha (Asian Journal of Chemistry, 2026)
In this study, 6,9-bis(carboxymethyl)-3-(2-((4-hydroxyphenethyl)amino)-2-oxoethyl)-14-(4-hydroxyphenyl)-11-oxo-3,6,9,12-tetraazatetra-decanoic acid (DTPATY) was synthesized through the condensation of DTPA bisanhydride with tyramine in DMF under a nitrogen atmosphere. The corresponding metal complexes, [M(DTPATY)Cl2] (M = Fe2+, Cu2+, Co2+, Ni2+, Mg2+ and Mn2+), were prepared using NaHCO3 under similar condensation conditions. The synthesized ligand and metal complexes were characterized by ESI-MS, elemental (CHN) analysis, FT-IR, UV-Vis and photoluminescence spectroscopy, while the ligand was further characterized by 1H and 13C NMR spectroscopy and the metal complexes by ESR spectroscopy. The spectroscopic and analytical data confirmed the formation of the DTPATY ligand and its coordination with the respective metal ions. Frontier molecular orbital (FMO) parameters were evaluated using density functional theory (DFT) at the B3LYP/6-31G' level. The DTPATY ligand and its metal complexes exhibited favourable water solubility, distinct optical properties and low cytotoxicity, with the PL studies providing evidence of their fluorescence characteristics.